The Influence of Entrepreneurs’ Online Popularity and Interaction Behaviors on Individual Investors’ Psychological Perception: Evidence From the Peer-To-Peer Lending Market - An, Jiaji; Di, He; Liu, Guoliang (Frontiers in Psychology, 2022)
Inappropriate social interactions of entrepreneurs can generate negative effects in the peer-to-peer lending market. To address this problem and assist peer-to-peer entrepreneurs in customizing their online interaction strategies, we used the cutting-edge cognitive-experiential self-system conceptual model and studied the relationship between peer-to-peer entrepreneurs’ interactions and financing levels. Online interactive information was categorized as emotional or cognitive, adding the moderator of entrepreneur popularity, and the effect of these interactions on individual investors was analyzed. We found that the entrepreneurs' online interactive information affected psychological perception of entrepreneurs and their corresponding brand image. The interaction between popularity and interactive information types was significant. The findings imply that less popular entrepreneurs should engage in emotional interactions, while more popular entrepreneurs should choose cognitive interactions. Online interaction created comparative advantages in the financing activities of peer-to-peer companies. These results expand understanding of the psychological facets of the consumer–brand relationship in the digital world, and extend the current literature. This study also highlights key areas of learning and application for both practitioners and scholars of organizational psychology.